SISTEM PAKAR DIAGNOSA PENYAKIT KUCING DENGAN METODE FORWARD CHAINING BERBASIS WEB - Bryant Arisandy, Kartika Imam Santoso, Cisillia Sundari, Edi Widodo (TRANSFORMASI, 2021)
The purpose of this research is to design and build the Expert System for Diagnosis Disease of Cats Using the Method of Forward Chaining Web-Based. The development method used is the method of ESDLC and inference engine Forward Chaining. The algorithm used by researchers in this expert system uses an Algorithm Depth-First Search (DFS). The results of this research are expert systems that can diagnose the disease and Treatment how to handle it. Keywords: Cat Disease, DFS, ESDLC, Expert System, Forward Chaining.